Gap Junctions Link Regular-Spiking and Fast-Spiking Interneurons in Layer 5 Somatosensory Cortex - Hatch, Robert J.; Mendis, G. Dulini C.; Kaila, Kai; Reid, Christopher A.; Petrou, Steven (Frontiers in Cellular Neuroscience, 2017)
Gap junctions form electrical synapses that modulate neuronal activity by synchronizing action potential firing of cortical interneurons. Gap junctions are thought to form predominantly within cortical interneurons of the same functional class and are therefore considered to act within discrete neuronal populations. Here, we challenge that view and show that the probability of electrical coupling is the same within and between regular-spiking and fast-spiking cortical interneurons in 16-21 days old mice. Firing properties of these two populations were distinct from other interneurons types including neurogliaform and low-threshold spiking cells. We also demonstrate that pre-junctional action potentials can depolarize post-junctional neurons and increase the probability of firing. Our findings of frequent gap junction coupling between functionally distinct interneuron subtypes suggest that cortical interneuron networks are much more extensive and heterogeneous than previously thought. This may have implications on mechanisms ranging from cognitive functions to modulation of pathological states in epilepsy and other neurological disorders.